Spermatogenesis in Triatoma melanocephala (Hemiptera: Triatominae) - Alevi, K. C. C. [UNESP]; Mendonca, P. P. [UNESP]; Pereira, N. P. [UNESP]; Rosa, João Aristeu da [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP] (Funpec-editora, 2013)
Triatoma melanocephala is a rare species of Hemiptera. It belonged to the Brasiliensis subcomplex and presents morphological characteristics very close to those of Triatoma vitticeps. We investigated spermatogenesis of T. melanocephala and compared it with that of T. vitticeps in order to determine whether these organisms have similar cytogenetic characteristics. Lacto-acetic orcein staining was used to observe all stages of meiosis. These two species were found to have the same karyotype (2n = 20A + X1X2X3Y), heteropycnotic corpuscles in the polyploid spermatogonial cells, interfasic and profasic nucleus, and chromocenter with four sex chromosomes during prophase. Thus, we conclude that besides the morphologic similarity of T. melanocephala with T. vitticeps, they also have similar spermatogenesis and cytogenetics.
Keywords: Triatomine; Cytogenetic; Meiosis; Lacto-acetic orcein; Brasiliensis subcomplex